Textiles for Functional Applications - Kumar, Bipin (IntechOpen, 2021)
This book offers a detailed understanding of the principles, procedures, equipment, and operation of selected technologies used to manufacture and evaluate intelligent multifunctional textiles and apparel goods. Leading experts from different domains of polymers, fiber production, nanotechnology, and textile chemical finishing address the entire production process by delving into crucial concepts and topics such as the development, characterization, and potential applications of functional materials. Textiles for Functional Applications is an excellent resource for researchers, designers, and academics who want to learn more about designing feasible functional textiles.